HUBUNGANPELAYANAN ANTENATAL CARE PADA IBU HAMIL DENGAN PEMILIHAN PENOLONG PERSALINAN DI PUSKESMAS PAGUYANGANKABUPATENBREBES - Yunita Bonis; Wilis Sukmaningtyas (Viva Medika, 2010)
Background: Maternal Mortality Rate (MMR) in 2011 in the State of Indonesia itself wasrated to 6 of the 10 countries with maternity coverage health personnel 73% (WHO 2011).From the initial survey conducted in Puskesmas Paguyangan on December 5, the dataobtained in October 2011 showed the number of K1 as many as 812 people (81.85%),deliveries by skilled health personnel as many as 707 people (74.66%), targets should be 947( 90%). Objective: To investigate the relationship between antenatal care to pregnant women withbirth attendants in health centers election Paguyangan Brebes in 2012 Methods: This research is an analytic correlation with cross sectional approach. Thesamples are Accedental sampling, using primary data. Samples were pregnant women by 30respondents. Research instrument was a questionnaire with data analysis using Fisher'sExact Test. Results: From the results, the majority of antenatal care is appropriate as much as 25respondents (83.3%), most choose birth attendants to use health personnel as much as 24respondents (80%), and the relationship between antenatal care to pregnant women withelection X2 values obtained birth attendants 13,500 (> X2 table) and pvalue 0.003> 0.05. Conclusion: There is a relationship between antenatal care to pregnant women with birthattendants election. Keywords: Antenatal Care, Childbirth Helper.